The impacts of international capital flows on household credits - Bilal Çayır (Central Bank Review (CBR), 2021)
This paper investigates the association between international capital flows (foreign direct investment and portfolio investments) and household credits using quarterly data for Turkey from 2005 to 2020. The Turkish financial market is a suitable sample due to Turkey's highly open economic structure to global markets and because of the country's strong demand dynamics. This study also employs a set of control variables in line with the existing literature and country-specific dynamics that might be related with household credit growth. Empirical findings show that (1) there is a unidirectional causal linkage from FDI and interest rates to household credits, (2) FDI and portfolio investments positively affect household credits in the long-run, (3) short-term results suggest a negative relationship between FDI and credit growth and (4), based on the results from the error correction model, a deviation in the household credit market is stabilized by 23.6% each quarter in order to achieve long-run equilibrium. The overall results of this study suggest that encouraging FDI inflows and thus accelerating the technological transformation of domestic markets may contribute to the development of the household credit market and indirectly to the welfare of households in Turkey.
Keywords: 330; Foreign direct investment; Household credits; Portfolio investment; Time series analysis